The Peptide Vaccine Combined with Prior Immunization of a Conventional Diphtheria-Tetanus Toxoid Vaccine Induced Amyloid β Binding Antibodies on Cynomolgus Monkeys and Guinea Pigs - Akira Yano; Kaori Ito; Yoshikatsu Miwa; Yoshito Kanazawa; Akiko Chiba; Yutaka Iigo; Yoshinori Kashimoto; Akira Kanda; Shinji Murata; Mitsuhiro Makino (Journal of Immunology Research)
The reduction of brain amyloid beta (Aβ) peptides by anti-Aβ antibodies is one of the possible therapies for Alzheimer’s disease. We previously reported that the Aβ peptide vaccine including the T-cell epitope of diphtheria-tetanus combined toxoid (DT) induced anti-Aβ antibodies, and the prior immunization with conventional DT vaccine enhanced the immunogenicity of the peptide. Cynomolgus monkeys were given the peptide vaccine subcutaneously in combination with the prior DT vaccination. Vaccination with a similar regimen was also performed on guinea pigs. The peptide vaccine induced anti-Aβ antibodies in cynomolgus monkeys and guinea pigs without chemical adjuvants, and excessive immune responses were not observed. Those antibodies could preferentially recognize Aβ40, and Aβ42 compared to Aβ fibrils. The levels of serum anti-Aβ antibodies and plasma Aβ peptides increased in both animals and decreased the brain Aβ40 level of guinea pigs. The peptide vaccine could induce a similar binding profile of anti-Aβ antibodies in cynomolgus monkeys and guinea pigs. The peptide vaccination could be expected to reduce the brain Aβ peptides and their toxic effects via clearance of Aβ peptides by generated antibodies.